Hydroxyl density measurement by two-beam UV-LED absorption spectroscopy in an atmospheric-pressure Ar-H2O2 vapor HF plasma jet - Wasin Nupangtha (2020)
© 2019, Chiang Mai University. All rights reserved. Atmospheric pressure plasma jets (APPJs) are sources of biologically active oxygen and nitrogen species. OH radical is one of the most reactive of Reactive oxygen species and plays crucial role in plasma chemistry at atmospheric pressure. The OH is also the precursor of hydrogen peroxide (H2O2), a major species responsible in part for plasma induced liquid phase reactivity. These experiments involve development setup of two-beam UV-LED absorption spectroscopy and its configuration. The OH densities are obtained by broadband UV absorption in a 330 kHz radio-frequency (rf) driven APPJ device operated with H2O2 vapor admixed to Argon with variation of rf powers. The use of a high intensity around 310 nm light-emitting diode as a light source and a light source and a 300 mm Czerny-Turner spectrometer 300i made the estimation of the total OH density possible by simultaneously measuring the absorption rates of different spectrally resolved rotational lines of the OH(A-X) transition.